Chinese as a Cultural Capital: The Case Study of Chinese Heritage Language Learners - Budi Kurniawan; Setefanus Suprajitno (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2019)
Chinese language education in Indonesia is closely related to the social, political, and cultural dimensions of the country. The change of power in the country in 1998 affected the development of Chinese language. Since the ban imposed on Chinese language and culture since 1965 was lifted, there have been an increasing number of Chinese language schools. Under the theoretical frameworks of Gardner’s motivational orientations and Bourdieu’s cultural capital, this study explored varied motivations of Chinese Indonesians to learn Chinese, and how their perception of China influenced their efforts in learning the language. Data were obtained through focus group discussions and interviews. The findings showed that integrative and instrumental orientations were found among participants, but due to the learners’ social milieu, instrumentality of Chinese dominated their orientations. The instrumentality of Chinese and the positive perception of China worked together to make Chinese language as a cultural capital for these CHL learners.